Quasi-adat: An Ethnographic Study of Palm Oil Plantation in Bawan Village - Indrizal, Edi; Ermayanti, Ermayanti; Irwandi, Ade (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This paper highlights cultural issues arising from oil palm plantations and efforts to preserve customs amid global change. The purpose of this study is to examine complex issues and efforts to preserve customs in the context of oil palm plantations in Agam Regency. The method used is critical ethnography to uncover cultural practices that can shape and perpetuate injustice, as well as how dominant groups maintain their power (quasi-customary). The land ownership system is based on Babingkah Tanah (Entity Ownership). Therefore, only Basa Nan Barampek and Penghulu Nan Batujah have authority over customary land. However, not all Ninik Mamak were involved in the transfer of customary land to PT AMP Plantation. Thus, the land transfer was carried out with customary and political elements to control the land by PT AMP Plantation and to approach only the dominant Ninik Mamak.